Perempuan, Kebaya, Dan Narasi Visual: Studi Penciptaan Karya Kolase Digital Bergaya Lowbrow Art - Faisal Akbar (Institut Seni Indoensia Surakarta, 2025)
This study explores the process of creating digital collage artworks themed around women in kebaya in the modern era, focusing on the transformation of kebaya as a symbol of identity, empowerment, and resistance among Indonesian women. Once a traditional garment, the kebaya has undergone a shift in function, now serving as a part of contemporary lifestyle expression. This research responds to that phenomenon through a practice-based art approach, adopting Alma M. Hawkins' three-phase creative method: exploration, improvisation, and formation. The exploration phase involved investigating Javanese and Encim kebaya as representations of two distinct yet equally powerful cultural identities. The improvisation phase developed visual sketches and experimented with digital collage techniques using graphic design software. The formation phase synthesized all visual elements into cohesive, communicative compositions. The result is two main works titled Motherland in Kebaya: Java Vibes and Motherland in Kebaya: Encim Vibes, each portraying the identity of Javanese women and Chinese-Betawi Peranakan women through figurative visual approaches and lowbrow art style. The first work presents kebaya as a symbol of cultural resistance against colonialism, while the second emphasizes the Encim kebaya as a symbol of hybrid cultural identity that continues to thrive amid globalization. The digital collage medium enables the fusion of traditional and contemporary elements into a unified visual narrative. This study demonstrates that visual art can serve as a reflective medium to depict the dynamics of cultural identity and opens new space for kebaya as a flexible and relevant cultural artifact. Thus, the artworks produced carry not only aesthetic value but also social critique and cultural meaning.